2016
DOI: 10.1080/2162402x.2016.1199311
|View full text |Cite
|
Sign up to set email alerts
|

Retargeting cytokine-induced killer cell activity by CD16 engagement with clinical-grade antibodies

Abstract: Cytokine-induced Killer (CIK) cells are a heterogeneous population of ex vivo expanded T lymphocytes capable of MHC-unrestricted antitumor activity, which share phenotypic and functional features with both NK and T cells. Preclinical data and initial clinical studies demonstrated their high tolerability in vivo, supporting CIK cells as a promising cell population for adoptive cell immunotherapy. In this study, we report for the first time that CIK cells display a donor-dependent expression of CD16, which can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 30 publications
5
39
0
Order By: Relevance
“…To sum up, the combination of CIK cells and human monoclonal antibodies showed promising results in vitro. Our findings confirm the works of Cappuzzello et al who recently reported that CIK cells are capable of ADCC and their cytolytic activity increased when monoclonal antibody was added (26). This opens up a variety of combinations between CIK cells and different monoclonal antibodies such as anti-CD137, anti-CD134 (OX40), anti-CD152 (CTLA-4), anti-PD-1 and anti-PD-L1.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To sum up, the combination of CIK cells and human monoclonal antibodies showed promising results in vitro. Our findings confirm the works of Cappuzzello et al who recently reported that CIK cells are capable of ADCC and their cytolytic activity increased when monoclonal antibody was added (26). This opens up a variety of combinations between CIK cells and different monoclonal antibodies such as anti-CD137, anti-CD134 (OX40), anti-CD152 (CTLA-4), anti-PD-1 and anti-PD-L1.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, human monoclonal antibodies might be able to induce antibody-dependent cell-mediated cytotoxicity (ADCC). It has already been reported that CD3 + CD56 + cells express CD16 and therefore ADCC might be a possible mechanism on how CIK cells perform their enhanced cytolytic activity in our work (26). Since monoclonal antibodies such as rituximab and ipilimumab have already been approved as therapeutic reagents against few malignant diseases new approaches targeting other molecules than CD20 and CTLA-4 have now become the focus of study.…”
Section: Discussionmentioning
confidence: 66%
“…Here, we have tested the ability of cytokine-inducedkiller T-lymphocytes (CIK) engineered with a TA-specific CAR to target tumor cells obtained by multiple STS hystotypes in vitro and in vivo. CIK are patient-derived polyclonal T-NK lymphocytes endowed with HLA class I-independent antitumor activity, mediated mostly by the interaction of their NKG2D receptor with stressinducible targets (MIC A/B; ULBPs 1-6) on tumor cells (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). To increase their tumor cell specificity, CIK were engineered with a TA-specific CAR.…”
Section: Introductionmentioning
confidence: 99%
“…Data highlighted that there is no correlation between the expression level of CD16a and the cytotoxicity outcome, and that the ADCC is accountable to the CD3 + CD56 + CD16 + subpopulation and not to the residual NK cells or TCR Îł/ÎŽ subset. 10 This therapeutic concept is exploited here as a novel option to treat primary and metastatic TNBC. The advantages of this combination therapy employs a clinical-grade mAb already widely used in clinics, such as cetuximab, whose usage could now find a much wider range of application than the registered therapeutic indications, because it is mainly exploited for its targeting and opsonizing properties and the capacity to trigger ADCC phenomena upon engagement of CD16a expressing cells.…”
Section: Discussionmentioning
confidence: 99%
“…CIK cells were obtained from PBMCs of healthy donors isolated by means of Ficoll-Paque PLUS (GE Healthcare) density gradient centrifugation, according to standard protocols. 10 PBMCs were plated in RPMI 1640 (Euroclone) supplemented with 10% heat-inactivated FBS (Gibco), 1% Ultraglutamine, 1% Hepes buffer, 1% penicillin/streptomycin (all from Lonza), at 37°C and 5% CO 2 , and stimulated with rhIFN-Îł (PeproTech) at 1000 U/ml at day 0. Twenty-four hours later, anti-CD3 mAb (OKT-3, Ortho Biotech Inc) at 50 ng/ml and rhIL-2 (Proleukin, Novartis) at 500 IU/ml were added to the culture medium; every 2-3 days medium was replenished and fresh rhIL-2 at 500 IU/ml was added.…”
Section: Generation and Characterization Of Cik Cellsmentioning
confidence: 99%